High frequency of mitochondrial DNA mutations in HIV‐infected treatment‐experienced individuals. Issue 1 (22nd June 2016) - Li, M; Foli, Y; Liu, Z; Wang, G; Hu, Y; Lu, Q; Selvaraj, S; Lam, W; Paintsil, E
Abstract : Objectives: We recently observed a decrease in deoxyribonucleotide (dNTP) pools in HIV‐infected individuals on antiretroviral therapy (ART). Alterations in dNTPs result in mutations in mitochondrial DNA (mtDNA) in cell culture and animal models. Therefore, we investigated whether ART is associated with mitochondrial genome sequence variation in peripheral blood mononuclear cells (PBMCs) of HIV‐infected treatment‐experienced individuals. Methods: In this substudy of a case−control study, 71 participants were included: 22 'cases', who were HIV‐infected treatment‐experienced patients with mitochondrial toxicity, 25 HIV‐infected treatment‐experienced patients without mitochondrial toxicity, and 24 HIV‐uninfected controls. Total DNA was extracted from PBMCs and purified polymerase chain reaction (PCR) products were subjected to third‐generation sequencing using the PacBio Single Molecule Real‐Time (SMRT) sequencing technology. The sequences were aligned against the revised Cambridge reference sequence for human mitochondrial DNA (NC_012920.1) for detection of variants. Results: We identified a total of 123 novel variants, 39 of them in the coding region. HIV‐infected treatment‐experienced patients with and without toxicity had significantly higher average numbers of mitochondrial variants per participant than HIV‐uninfected controls. We observed a higher burden of mtDNA large‐scale deletions in HIV‐infected treatment‐experienced patients with toxicity compared with HIV‐uninfected controls ( P = 0.02). The frequency of mtDNA molecules containing a common deletion (mt.δ4977) was higher in HIV‐infected treatment‐experienced patients with toxicity compared with HIV‐uninfected controls ( P = 0.06). There was no statistically significant difference in mtDNA variants between HIV‐infected treatment‐experienced patients with and without toxicity. Conclusions: The frequency of mtDNA variants (mutations and large‐scale deletions) was higher in HIV‐infected treatment‐experienced patients with or without ART‐induced toxicity than in uninfected controls.